Binder for anode of secondary battery, anode of secondary battery, and secondary battery

By using adhesives prepared with copolymers with high energy storage modulus at 100°C, the problems of reducing adhesive strength and shortening of battery life caused by volume changes in the anode active material of the secondary battery are solved, and high elasticity and excellent processing performance are achieved at the actual use temperature.

CN115176361BActive Publication Date: 2025-04-22LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180017367.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-25
Filing Date
2021-11-26
Publication Date
2025-04-22
Estimated Expiration
2041-11-26

AI Technical Summary

Technical Problem

The volume of the anode active material of the secondary battery changes severely during charging and discharging, resulting in a reduced adhesive force and a shortened battery life. The prior art is difficult to provide an elastic adhesive sufficient to withstand such changes.

Method used

A copolymer with an energy storage modulus of 100 MPa or more was used as the binder for the anode, and a binder in the form of latex particles was prepared by an emulsion polymerization preparation method to improve processing performance and elasticity.

Benefits of technology

The adhesive has excellent elasticity within the actual temperature range of use, can withstand volume changes of the anode active material, improve the processing performance of the anode, and ultimately ensure the life of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003818426140000191
    Figure BDA0003818426140000191
  • Figure BDA0003818426140000201
    Figure BDA0003818426140000201
Patent Text Reader

Abstract

This disclosure relates to an adhesive for an anode of a secondary battery, the anode of the secondary battery, and the secondary battery. Specifically, an adhesive for an anode is provided that has sufficient elasticity to withstand volume changes in the anode active material while improving processability, and that the adhesive can ultimately ensure the lifespan of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2020-0163138 filed in the Korean Intellectual Property Office on November 27, 2020, and Korean Patent Application No. 10-2021-0164756 filed in the Korean Intellectual Property Office on November 25, 2021, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present disclosure relates to a binder for an anode of a secondary battery, an anode of a secondary battery, and a secondary battery. Background Art

[0004] Secondary batteries have attracted attention as power sources not only for small electronic devices such as portable computers, portable phones, and cameras, but also for large electronic devices such as electric cars and power storage devices.

[0005] The anode of the secondary battery includes a current collector and an anode active material layer, wherein the anode active material layer contains an anode active material.

[0006] Specifically, various types of carbon-based materials including artificial graphite, natural graphite, and hard carbon capable of inserting / desorbing lithium have been used as anode active materials, and research is also being conducted on using silicon, tin, silicon-tin alloys, etc. as anode active materials to increase discharge capacity.

[0007] However, as the discharge capacity of the anode active material increases, the volume change caused by charge and discharge becomes serious, thereby causing problems of weakening the binding force of the anode and reducing the life of the secondary battery.

[0008] In this regard, a binder having sufficient elasticity to withstand the volume change of the anode active material is required. Specifically, in order to ensure the life of the secondary battery, an adhesive having appropriate elasticity within the actual use temperature range of the battery must be applied to the anode. In addition, an adhesive having high elasticity also needs to ensure processing performance when manufacturing the anode. Summary of the invention

[0009] Technical issues

[0010] In the present disclosure, a binder for an anode is provided, which has elasticity sufficient to withstand volume change of an anode active material while improving processability and which can ultimately ensure the life of a secondary battery.

[0011] Technical Solution

[0012] Specifically, in an embodiment of the present disclosure, provided are a binder for an anode of a secondary battery having an excellent elastic modulus in a practical use temperature range, an anode mixture including the binder, an anode, and a secondary battery.

[0013] Specifically, in one embodiment of the present disclosure, there is provided a binder for an anode of a secondary battery, comprising a (co)polymer having a storage modulus of 100 MPa or more measured at 100°C.

[0014] In another embodiment of the present disclosure, there is provided a method for preparing the above-mentioned binder for an anode, the method comprising the step of preparing a (co)polymer by emulsion polymerizing a monomer mixture in the presence of an emulsifier and a polymerization initiator.

[0015] In another embodiment of the present disclosure, an anode mixture for a secondary battery is provided, comprising the above binder for an anode of a secondary battery and an anode active material.

[0016] In another embodiment of the present disclosure, there is provided an anode of a secondary battery, including: an anode mixture layer including the anode mixture; and an anode current collector.

[0017] In another embodiment of the present disclosure, a secondary battery including the above-mentioned anode is provided.

[0018] Beneficial Effects

[0019] The binder for an anode of a secondary battery according to one embodiment has elasticity sufficient to withstand volume changes of an anode active material while improving processability, particularly having appropriate elasticity within an actual use temperature range of the battery, thereby ultimately ensuring the life of the secondary battery. DETAILED DESCRIPTION

[0020] In the present disclosure, the terms “first”, “second”, etc. are used to describe various components, and these terms are only used to distinguish a certain component from other components.

[0021] The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. Singular forms are also intended to include plural forms, unless the context clearly states otherwise. It should also be understood that when used in the present disclosure, the terms "include", "have" or "have" indicate the presence of the features, quantities, steps, components or combinations thereof, but do not exclude the presence or addition of one or more other features, quantities, steps, components or combinations thereof.

[0022] Furthermore, as used herein, when a layer or element is referred to as being formed “on” or “over” a layer or element, the layer or element may be directly formed on the layer or element, or other layers or elements may be additionally formed between layers, on an object, or on a substrate.

[0023] Since the present invention can be variously modified and has various forms, its specific embodiments are shown by way of example and will be described in detail. However, this does not mean that the present invention is limited to the disclosed specific forms, and it should be understood that the present invention is included in all modifications, equivalents and substitutions within the thought and technical scope of the present invention.

[0024] Binder for anode of secondary battery

[0025] In one embodiment of the present disclosure, provided is a binder for an anode of a secondary battery, the binder comprising a (co)polymer having a storage modulus of 100 MPa or more measured at 100° C.

[0026] Properties of Binders for Anodes

[0027] Viscous and elastic properties are calculated using dynamic mechanical analysis by measuring the restoring force or strain when external changes are applied, and the elastic modulus measured is a complex number composed of the storage modulus and the loss modulus. The higher the storage modulus, the closer it is to a perfect elastomer. The mechanical properties of a polymer change depending on the degree of motion of the polymer chain. As the temperature increases, the motion of the polymer chain increases, so the mechanical properties decrease. In particular, the degree of reduction in mechanical properties becomes very large below and above the glass transition temperature of the polymer.

[0028] Here, the storage modulus represents the elastic component of strain energy that can be accumulated as stress in the material.

[0029] In addition, generally, the storage modulus decreases as the temperature increases. If the anode binder according to one embodiment includes a (co)polymer, the storage modulus does not significantly decrease even when the temperature increases.

[0030] In order to confirm whether the binder for an anode according to the embodiment has appropriate elasticity within the actual use temperature range of a battery, the storage modulus of the (co)polymer may be measured at 100°C.

[0031] Specifically, for the binder for an anode according to the embodiment, the viscoelastic behavior of the film with respect to dynamic deformation may be measured to obtain the storage modulus of the (co)polymer at 100°C.

[0032] According to one embodiment, the storage modulus can be measured by applying a shear strain with a frequency of 1 Hz and a strain amplitude of 0.1% to a film having a thickness of less than 2 mm comprising a (co)polymer, while increasing the temperature in the temperature range of -60°C to 100°C and at a heating rate of 5°C / min.

[0033] More specifically, the film-shaped sample can be prepared by drying the binder for anode according to the embodiment to form a film having a thickness of 2 mm or less, and then punching the film into a rectangle of 18 mm (length)*6 mm (width).

[0034] In addition, a thin film sample can be placed in a dynamic mechanical analyzer (manufactured by TA Instrument), and the temperature can be increased at 5°C / min at a frequency of 1 Hz in the film stretching mode to measure the viscoelastic behavior for dynamic deformation with a shear strain of 0.1% at each measuring temperature (-60°C to 100°C).

[0035] For the binder for anode according to the embodiment, the viscoelastic behavior of the film for dynamic deformation is measured by the above method to obtain the storage modulus measured at 100° C., which may be 100 MPa or more, 102 MPa or more, 105 MPa or more, or 108 MPa or more. The upper limit is not particularly limited, but may be 500 MPa or less, 400 MPa or less, 350 MPa or less, or 300 MPa or less.

[0036] If the storage modulus of the (co)polymer measured at 100°C is above 100 MPa, the binder can withstand the different volume changes of the anode active material when preparing the anode of the secondary battery, so as to improve the processing performance, thereby giving the best elasticity within the actual use temperature range and ensuring the life of the secondary battery. In addition, it also has the effect of suppressing the thickness expansion of the electrode.

[0037] In addition, in order to confirm whether the binder for an anode according to the embodiment has suitable viscoelastic properties within the actual use temperature range of the battery, the viscoelastic behavior of the film with respect to dynamic deformation can be measured to obtain the maximum peak temperature (Tp) of the viscoelastic loss factor (tan δ).

[0038] Specifically, the viscoelastic behavior of the film with respect to dynamic deformation can be measured by the same method as the storage modulus measurement.

[0039] For the binder for anode according to the embodiment, the maximum peak temperature (Tp) of the viscoelastic behavior of the film for dynamic deformation to obtain the viscoelastic loss factor (tan δ) measured by the above method may be 0° C. or less, -3° C. or less, -6° C. or less, or -9° C. or less. There is no particular limitation on the lower limit, but it may be -60° C. or more, -50° C. or more, -40° C. or more, or -30° C. or more.

[0040] Therefore, according to one embodiment, the glass transition temperature of the (co)polymer may be from -60°C to 0°C.

[0041] Furthermore, according to one embodiment, the ratio of the storage modulus measured at 100°C to the storage modulus at the glass transition temperature of the (co)polymer may be 10% or more. More specifically, the ratio of the storage modulus may be 12% or more, or 15% or more.

[0042] The binder for the anode according to the embodiment can satisfy the storage modulus and thus have elasticity sufficient to withstand the volume change of the anode active material while improving processing performance, especially having appropriate elasticity within the actual use temperature range of the battery, thereby ultimately ensuring the life of the secondary battery.

[0043] Type and content of repeating units

[0044] The binder for the anode may include a (co)polymer in which the type and content of the repeating unit are each controlled within a specific range.

[0045] In the present disclosure, a (co)polymer may refer to a polymer or a copolymer.

[0046] Specifically, based on the total weight of repeating units (100 wt %), the copolymer may contain: a) 35 wt % to 60 wt % of a first repeating unit from an aliphatic conjugated diene first monomer, b) 0.1 wt % to 25 wt % of a second repeating unit from an aromatic vinyl second monomer, c) 10 wt % to 35 wt % of a third repeating unit from a nitrile third monomer, and d) 15 wt % to 35 wt % of a fourth repeating unit from an unsaturated carboxylic acid fourth monomer.

[0047] The glass transition temperature of the (co)polymer may be between -60°C and 0°C.

[0048] In particular, the third repeating unit may be a monomer including both an ethylenically unsaturated group and a nitrile group in a molecule, and may improve hardness, strength, and elastic modulus, thereby contributing to improving the life of the electrode.

[0049] However, the effect of the third repeating unit can only be shown when the content of the third repeating unit is 10 wt % to 35 wt % based on the total weight of the repeating unit (100 wt %). When the content of the third repeating unit is less than 10 wt %, the effect is not obvious, and when it exceeds 35 wt %, the strength of the adhesive itself is reduced, resulting in reduced adhesion and reduced life problems.

[0050] Meanwhile, the first repeating unit may play a role in improving the adhesive force between the anode active material and the current collector, and the second repeating unit and the fourth repeating unit may play a role in increasing the strength of the binder.

[0051] In this regard, even if the content of the third repeating unit satisfies 10 wt % to 35 wt %, when any one of the first to third repeating units is replaced with another material, or does not satisfy the defined content range of the embodiment (including the case where it is not included), the anode adhesion may decrease or the capacity retention rate may decrease.

[0052] Therefore, when the respective content ranges satisfy the defined ranges of the embodiment while including all of the first to fourth repeating units, the functions of the repeating units may be coordinated to provide elasticity sufficient to withstand volume changes of the anode active material while improving processability.

[0053] Specifically, the binder for an anode of the embodiment may have appropriate elasticity within the actual use temperature range of the battery and may ensure the life of the secondary battery even when used with a silicon-based anode active material and a carbon-based anode active material that exhibit severe volume expansion.

[0054] Hereinafter, each repeating unit will be described in more detail.

[0055] The first repeating unit

[0056] The first repeating unit may be derived from an aliphatic conjugated diene-based first monomer. Specifically, the first repeating unit corresponds to a structural unit of a (co)polymer formed by adding the aliphatic conjugated diene-based first monomer during polymerization.

[0057] When the first repeating unit is included in the (co)polymer, the binder for the anode of the embodiment can inhibit the electrolyte swelling phenomenon at high temperature, and can have elasticity due to the rubber component, thereby reducing the thickness of the anode, reducing the gas generation phenomenon, and is also used to improve the adhesion, thereby maintaining the adhesion between the anode active material and the current collector.

[0058] As the first monomer, an aliphatic conjugated diene monomer, an aliphatic conjugated diene compound having 2 to 20 carbon atoms can be used. As a non-limiting example, the aliphatic conjugated diene first monomer can be selected from 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,2-dimethyl-1,3-butadiene, 1,4-dimethyl-1,3-butadiene, 1-ethyl-1,3-butadiene, 2-phenyl-1,3-butadiene, 1,3-pentadiene, 1,4-pentadiene, 3-methyl- At least one of 1,3-pentadiene, 4-methyl-1,3-pentadiene, 2,4-dimethyl-1,3-pentadiene, 3-ethyl-1,3-pentadiene, 1,3-hexadiene, 1,4-hexadiene, 1,5-hexadiene, 2-methyl-1,5-hexadiene, 1,6-heptadiene, 6-methyl-1,5-heptadiene, 1,6-octadiene, 1,7-octadiene and 7-methyl-1,6-octadiene. For example, 1,3-butadiene can be used as the aliphatic conjugated diene-based first monomer.

[0059] Based on the total weight of the repeating units (100 wt%), the content of the first repeating unit can be 35 wt% to 60 wt%. In other words, based on the total weight of the monomers when preparing the (co)polymer (100 wt%), the amount of the first monomer can be 35 wt% to 55 wt%.

[0060] For example, based on the total weight of the repeating units (100 wt %), the content of the first repeating unit can be greater than 35 wt %, greater than 37 wt %, greater than 39 wt %, or greater than 40 wt %, and less than 60 wt %, less than 58 wt %, less than 56 wt %, or less than 55 wt %.

[0061] If the content of the first repeating unit increases within the above range, the above effects on the first repeating unit can be increased. However, if the content of the first repeating unit exceeds 60 wt %, there is a problem that the strength of the resulting adhesive is reduced.

[0062] The second repeating unit

[0063] The second repeating unit is derived from an aromatic vinyl-based second monomer. Specifically, the second repeating unit corresponds to a structural unit of a (co)polymer formed by adding the above-mentioned second monomer during polymerization.

[0064] If the second repeating unit is included in the (co)polymer, the binder for an anode according to the embodiment may have improved strength.

[0065] The aromatic vinyl second monomer may be at least one selected from styrene, α-methylstyrene, β-methylstyrene, p-tert-butylstyrene, chlorostyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene and divinylbenzene, for example, styrene.

[0066] Based on the total weight of the repeating units (100 wt%), the content of the second repeating unit can be 0.1 wt% to 25 wt%. In other words, based on the total weight of the monomers when preparing the (co)polymer (100 wt%), the amount of the second monomer can be 0.1 wt% to 20 wt%.

[0067] For example, based on the total weight of the repeating units (100 wt %), the content of the second repeating unit can be greater than 0.1 wt %, greater than 0.5 wt %, greater than 1 wt %, or greater than 2 wt %, and less than 25 wt %, less than 23 wt %, less than 21 wt %, or less than 20 wt %.

[0068] If the content of the second repeating unit increases within the above range, the above effect on the second repeating unit can be increased. However, if the content of the second repeating unit in the (co)polymer is greater than 25% by weight, there will be a problem of reducing the fluidity of the adhesive or reducing the bonding strength.

[0069] The third repeating unit

[0070] The third repeating unit is derived from a nitrile third monomer. Specifically, the third repeating unit corresponds to a structural unit of a (co)polymer formed by adding the third monomer during polymerization.

[0071] The nitrile third monomer may be at least one selected from acrylonitrile, methacrylonitrile and allyl cyanide, for example, may be acrylonitrile.

[0072] Based on the total weight of the repeating units (100 wt%), the content of the third repeating unit may be 10 wt% to 35 wt%. In other words, based on the total weight of the monomers when preparing the (co)polymer (100 wt%), the amount of the third monomer may be 15 wt% to 35 wt%.

[0073] For example, based on the total weight of the repeating units (100 wt %), the content of the third repeating unit can be greater than 10 wt %, greater than 11 wt %, greater than 13 wt %, or greater than 15 wt %, and less than 35 wt %, less than 30 wt %, less than 28 wt %, or less than 25 wt %.

[0074] If the content of the third repeating unit increases within the above range, the above effect on the third repeating unit can be increased. However, if the content of the third repeating unit in the (co)polymer is greater than 35% by weight, there will be a problem of reducing the fluidity of the adhesive or reducing the bonding strength.

[0075] The fourth repeating unit

[0076] The fourth repeating unit is derived from an unsaturated carboxylic acid-based fourth monomer. Specifically, the fourth repeating unit corresponds to a structural unit of a (co)polymer formed by adding the fourth monomer during polymerization.

[0077] If the fourth repeating unit is included in the (co)polymer, the binder for an anode according to the embodiment may have improved strength, and improved polymerization and storage stability.

[0078] The unsaturated carboxylic acid-based fourth monomer may be at least one selected from acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, tetrahydrophthalic acid, crotonic acid, isocrotonic acid and nadic acid, for example, acrylic acid.

[0079] Based on the total weight of the repeating units (100 wt%), the content of the fourth repeating unit may be 15 wt% to 35 wt%. In other words, based on the total weight of the monomers when preparing the (co)polymer (100 wt%), the amount of the fourth monomer may be 15 wt% to 35 wt%.

[0080] For example, based on the total weight of the repeating units (100 wt %), the content of the fourth repeating unit can be greater than 15 wt %, greater than 17 wt %, greater than 19 wt %, or greater than 20 wt %, and less than 35 wt %, less than 33 wt %, less than 31 wt %, or less than 30 wt %.

[0081] If the content of the fourth repeating unit increases within the above range, the above-mentioned effect about the fourth repeating unit can be increased. However, if the content of the fourth repeating unit in the (co)polymer is greater than 35% by weight, there will be a problem of reducing the fluidity of the adhesive or reducing the affinity with the electrolyte.

[0082] Average particle size of polymer (latex particles)

[0083] Meanwhile, in the binder for an anode according to the embodiment, the (co)polymer may be in the form of latex particles prepared by emulsion polymerization.

[0084] The (co)polymer may be a latex particle having an average particle size of 50 nm to 500 nm.

[0085] The average particle size of latex particles can be more than 50nm, more than 70nm or more than 100nm, and less than 500nm, less than 400nm, less than 300nm or less than 200nm. If the average particle size of latex particles is too small, viscosity will increase and the adhesive force of the mixture layer containing it and the current collector will weaken. On the contrary, if the average particle size of latex particles is too large, the stability of particles will decrease.

[0086] The average particle diameter of the latex particles can be measured using a particle size analyzer (NICOMP AW380, manufactured by PSS) using a dynamic light scattering method.

[0087] Specifically, in the present disclosure, "average particle size" may refer to the arithmetic mean particle size in a particle size distribution measured by a dynamic light scattering method. Here, the arithmetic mean particle size may be measured by the average particle size of a scattering intensity distribution, the average particle size of a volume distribution, or the average particle size of a number distribution, preferably by the average particle size of a scattering intensity distribution.

[0088] For example, after each binder for anode is diluted so that the intensity value measured at room temperature is about 300 (KHz), the average particle diameter of the scattered intensity distribution can be measured according to the dynamic light scattering method using a particle size analyzer (NICOMP AW380, manufactured by PSS Corporation).

[0089] Aqueous solvent

[0090] In addition, an aqueous solvent, ie, water, may be added to the binder for an anode according to the embodiment in addition to the above-mentioned (co)polymer, ie, latex particles.

[0091] In terms of controlling the stability and viscosity of the latex particles, the amount of the aqueous solvent may be about 50 parts by weight to about 1,000 parts by weight, specifically about 100 parts by weight to about 400 parts by weight, based on 100 parts by weight of the (co)polymer. For example, based on the total amount (100 wt%) of the binder for the anode according to the embodiment, the total solid content (TSC) may be adjusted to about 10 wt% to about 65 wt%.

[0092] If the aqueous solvent is used too little, there is a problem of reducing the stability of the latex particles. If the solvent is used too much, there is a problem of reducing the viscosity, weakening the adhesion of the binder and reducing the overall performance of the battery.

[0093] Method for preparing binder for anode of secondary battery

[0094] In another embodiment of the present disclosure, a method of preparing the binder for an anode according to the above embodiment using emulsion polymerization is provided.

[0095] Specifically, the emulsion polymerization may include a step of preparing a (co)polymer by emulsion polymerizing a monomer mixture in the presence of an emulsifier and a polymerization initiator.

[0096] More specifically, based on the total weight of the monomer mixture (100 wt %), the monomer mixture may contain: a) 35 wt % to 60 wt % of a first repeating unit from an aliphatic conjugated diene first monomer, b) 0.1 wt % to 25 wt % of a second repeating unit from an aromatic vinyl second monomer, c) 10 wt % to 35 wt % of a third repeating unit from a nitrile third monomer, and d) 15 wt % to 35 wt % of a fourth repeating unit from an unsaturated carboxylic acid fourth monomer.

[0097] Hereinafter, a preparation method of the embodiment will be described in detail, but a description overlapping with the above contents will be omitted.

[0098] Emulsion polymerization

[0099] In addition, emulsion polymerization can be performed by single polymerization or multi-stage polymerization. In this case, single polymerization may refer to a method in which the monomers used are put into a single reactor and polymerized simultaneously, and multi-stage polymerization may refer to a method in which the monomers used are polymerized sequentially in two or more stages.

[0100] If carried out by multi-stage polymerization, the emulsion polymerization may comprise the following steps:

[0101] In the presence of an emulsifier and a polymerization initiator, all of a) aliphatic conjugated diene first monomer, all of b) aromatic vinyl second monomer, all of c) nitrile third monomer and part of d) unsaturated carboxylic acid fourth monomer are first emulsion polymerized; and

[0102] After the first emulsion polymerization, the remaining d) unsaturated carboxylic acid fourth monomer is added, and then the second emulsion polymerization is carried out.

[0103] A portion of d) the unsaturated carboxylic acid fourth monomer in the first emulsion polymerization and the remaining d) the unsaturated carboxylic acid fourth monomer in the second emulsion polymerization may satisfy a weight ratio of 1:0.1 to 1:10, specifically 1:1 to 1:8, for example, 1:2.5 to 1:5.

[0104] In addition, emulsion polymerization can be performed in a solution containing the above-mentioned aqueous solvent in the presence of an emulsifier and a polymerization initiator.

[0105] The polymerization temperature and polymerization time of the emulsion polymerization for preparing the (co)polymer may be appropriately determined in some cases. For example, the polymerization temperature may be about 50° C. to about 200° C., and the polymerization time may be about 0.5 hour to about 20 hours.

[0106] Polymerization initiator

[0107] As the polymerization initiator available in the emulsion polymerization process, inorganic or organic peroxides can be used. For example, water-soluble initiators including potassium persulfate, sodium persulfate, ammonium persulfate, etc., and oil-soluble initiators including cumene hydroperoxide, benzoyl peroxide, etc. can be used.

[0108] Activator

[0109] In addition, an activator for promoting the initiation of the reaction of the peroxide may be further included together with the polymerization initiator, and the activator used here may be at least one selected from the group consisting of sodium formaldehyde sulfoxylate, sodium ethylenediaminetetraacetate, ferrous sulfate, and glucose.

[0110] Emulsifier

[0111] And, the emulsifier used for emulsion polymerization used herein can be anionic emulsifier, such as sodium dodecyl diphenyl ether disulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dioctyl sulfosuccinate, etc.; or nonionic emulsifier, such as polyoxyethylene alkyl ether such as polyoxyethylene lauryl ether, polyoxyethylene alkyl aryl ether, polyoxyethylene alkyl amine, polyoxyethylene alkyl ester, etc. The above-mentioned emulsifier can be a substance having both a hydrophilic group and a hydrophobic group, and in the process of emulsion polymerization, a micellar structure can be formed and the polymerization of each monomer can occur inside the micellar structure. Preferably, anionic emulsifiers and nonionic emulsifiers can be used alone or in combination of two or more types thereof, and the use of a mixture of anionic emulsifiers and nonionic emulsifiers can be more effective, but the present disclosure is not necessarily limited to this type of emulsifier.

[0112] And, the emulsifier may be used in an amount of about 0.01 to about 10 parts by weight, about 1 to about 10 parts by weight, or about 3 to about 5 parts by weight based on 100 parts by weight of all monomer components used in the preparation of the copolymer.

[0113] Anode mixture and anode

[0114] In other embodiments of the present disclosure, an anode mixture including the binder for an anode according to the above embodiment and an anode active material is provided, an anode mixture layer including the anode mixture, and an anode including an anode current collector are also provided.

[0115] The anode active material, the anode current collector, and the like used in the anode mixture and the anode may each include generally known components, except for the binder for the anode according to the embodiment.

[0116] anode

[0117] Based on the total weight of the anode mixture (100 wt%), the content of the binder for the anode according to the embodiment may be 1 wt% to 10 wt%, specifically 1 wt% to 5 wt%. When the above conditions are met, the content of the anode active material can be relatively increased, and the discharge capacity of the anode can be further improved.

[0118] Meanwhile, the binder for the anode according to the embodiment has excellent properties such as adhesion, mechanical properties, etc. Therefore, if a graphite-based anode active material is used as the anode active material of the anode mixture, and an anode active material having a higher capacity than the graphite-based anode active material is used, the adhesion between the anode active material and the anode active material, between the anode active material and the anode current collector, etc. can be maintained, and the expansion of the anode active material can be suppressed due to the mechanical properties themselves.

[0119] Since the binder for an anode according to the embodiment is applicable not only to a graphite-based anode active material but also to an anode active material having a higher capacity than the graphite-based anode active material, in one embodiment of the present disclosure, the type of the anode active material is not particularly limited.

[0120] Specifically, the anode active material may include carbon and graphite materials, such as natural graphite, artificial graphite, carbon fiber, non-graphitizable carbon, etc.; metals capable of alloying with lithium, such as Al, Si, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Pd, Pt, Ti, etc., and compounds containing these elements; composite materials of metals and their compounds with carbon and graphite materials; lithium-containing nitrides; titanium dioxide; lithium titanium oxide, etc., but not limited thereto. Among them, carbon-based active materials, silicon-based active materials, tin-based active materials, or silicon-carbon-based active materials are more preferred, and they can be used alone or in combination of two or more.

[0121] Typically, the anode current collector can be made to have a thickness of 3 μm to 500 μm. There is no particular limitation on this anode current collector, as long as it has conductivity and does not cause chemical changes to the battery, for example, it can be copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or stainless steel, aluminum-cadmium alloy, etc., surface-treated with carbon, nickel, titanium or silver. In addition, the adhesion of the anode active material can be increased by forming fine irregular bodies on the surface, and the anode current collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabric bodies, etc.

[0122] The anode can be prepared by applying an anode mixture containing an anode active material and a binder onto an anode current collector, drying, and rolling, and, if necessary, can be prepared by further adding a conductive material, a filler, etc.

[0123] Preferably, the anode can contain at least one anode active material selected from carbonaceous materials and silicon compounds.

[0124] Here, the carbonaceous material can be at least one material selected from natural graphite, artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fiber, mesocarbon microbeads, coke from petroleum or coal, soft carbon, and hard carbon as exemplified above. And, the silicon compound can include Si-containing compounds, i.e., Si, Si-C composite materials, SiOx (0 < x < 2), Si-Q alloys, mixtures thereof, or mixtures of at least one of them with SiO 2 mixtures.

[0125] The conductive material is used to impart conductivity to the anode, and any conductive material that does not cause a chemical change in the battery can be used. Examples thereof can include carbonaceous materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, single-walled carbon nanotube, multi-walled carbon nanotube, etc.; metal materials such as copper powder, nickel powder, aluminum powder, silver powder, metal fiber, etc.; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0126] The filler can optionally be used as a component for suppressing anode swelling, and there is no specific limitation as long as it is a fibrous material that does not cause a chemical change in the battery. For example, the materials used here can include olefinic polymers such as polyethylene, polypropylene, etc.; and fibrous materials such as glass fiber, carbon fiber, etc.

[0127] cathode

[0128] The cathode can include a cathode active material, and the cathode active material can include layered compounds such as lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), etc., or compounds substituted with one or more transition metals; lithium manganese oxides such as Li 1+x Mn 2-x O 4 (where x is from 0 to 0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 etc.; lithium copper oxide (Li 2 CuO 2); Vanadium oxides, such as LiV 3 O 8 、LiFe 3 O 4 、V 2 O 5 , Cu 2 V 2 O 7 etc.; LiNi 1-x M x O 2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, x = 0.01 to 0.3) as the representative of Ni-type lithium nickel oxide; LiMn 2-x M x O 2 (wherein, M = Co, Ni, Fe, Cr, Zn or Ta, x = 0.01 to 0.1), or Li 2 Mn 3 MO 8 (wherein M = Fe, Co, Ni, Cu or Zn) as the representative lithium manganese composite oxide; LiNi x Mn 2-x O 4 Lithium manganese composite oxides with spinel structure represented by LiMn 2 O 4 , wherein a portion of Li in the formula is replaced by an alkaline earth metal ion; disulfide; Fe 2 (MoO 4 ) 3 etc., but not limited to these.

[0129] Typically, the cathode current collector can be made to have a thickness of 3 μm to 500 μm. There is no particular limitation on this anode current collector, as long as it has high conductivity and does not cause chemical changes to the battery, for example, it can be stainless steel, aluminum, nickel, titanium, calcined carbon, aluminum, or stainless steel surface-treated with carbon, nickel, titanium or silver. The current collector can form fine irregular bodies on its surface to increase the adhesion of the cathode active material, and can have various forms, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabric bodies, etc.

[0130] There is no particular limitation on such a conductive material as long as it has conductivity and does not cause chemical changes to the battery, and the following materials can be used: for example, graphite, such as natural graphite, artificial graphite, etc.; carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, single-walled carbon nanotubes, multi-walled carbon nanotubes, etc.; conductive fibers, such as carbon fabrics, metal fabrics, etc.; metal powders, such as fluorocarbons, aluminum, nickel powder, etc.; conductive whiskers, such as zinc oxide, potassium titanate, etc.; conductive metal oxides, such as titanium oxide, etc.; conductive materials, such as polyphenylene derivatives; and the like.

[0131] Conventionally known binders can be used for cathodes. Representative examples thereof used herein may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylate styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.

[0132] The anode and cathode can be prepared by mixing the active material and the binder, in some cases the conductive material, the filler, etc. in a solvent to prepare a slurry electrode mixture, and then applying the electrode mixture to each electrode current collector. Since such an electrode preparation method is well known in the art, its detailed description will be omitted herein.

[0133] Secondary battery

[0134] In another embodiment of the present disclosure, a secondary battery including the anode according to the above embodiment is provided. This secondary battery may have a form including a cathode; an electrolyte; and an anode, and may be implemented as a lithium secondary battery.

[0135] A lithium secondary battery may be manufactured by impregnating an electrode assembly including a cathode, a separator, and an anode with a non-aqueous electrolyte.

[0136] The cathode and anode may be the same as described above.

[0137] In the case of a diaphragm, any one commonly used in lithium batteries can be used, which separates anode and cathode and provides a mobile channel for lithium ions. In other words, the diaphragm used herein can be a diaphragm with low resistance to the ion movement of the electrolyte and excellent electrolyte retention ability. For example, the diaphragm can be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE) or a combination thereof, and can also be in the form of a non-woven fabric or a woven fabric. For example, polyolefin polymer diaphragms such as polyethylene, polypropylene, etc. can be mainly used in lithium ion batteries, and a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, which can be optionally used in a single-layer or multilayer structure.

[0138] In some cases, a gel polymer electrolyte may be coated on the separator to increase battery stability. Representative examples of such gel polymers may include polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, and the like.

[0139] However, if a solid electrolyte is used instead of a nonaqueous electrolyte, the solid electrolyte can also be used as a separator.

[0140] The nonaqueous electrolyte may be a liquid electrolyte containing a nonaqueous organic solvent and a lithium salt. The nonaqueous organic solvent may serve as a medium through which ions participating in the electrochemical reaction of the battery may move.

[0141] Examples of solvents for non-aqueous electrolytes may include propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, γ-butyrolactone, ethylene sulfite, propylene sulfite, tetrahydrofuran, and mixtures thereof, specifically mixtures of chain carbonates such as ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc. and cyclic carbonates such as propylene carbonate, ethylene carbonate, etc., but the present disclosure is not limited thereto. There are no particular restrictions on lithium salts, as long as they are used in conventional lithium secondary batteries, for example, examples thereof may include lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ), lithium hexafluorophosphate (LiPF 6 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), Lithium Bis(trifluoromethanesulfonamide) (UN(CF 3 SO 2 ) 2 ) and mixtures thereof.

[0142] In addition, the electrolyte may also include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), fluoropropylene carbonate (FPC), propensultone (PRS), propane sultone (PS), lithium bis(oxalate)borate (LiBOB), lithium difluorobis(oxalate)phosphate (LiDFOP) or a mixture thereof, but is not limited thereto, to improve film formation and high temperature storage performance.

[0143] The lithium secondary battery according to the present disclosure may be used not only as a battery cell used as a power source for small devices but also as a unit battery in a medium or large battery module including a plurality of battery cells.

[0144] Hereinafter, preferred embodiments will be presented to better understand the present disclosure. However, the following embodiments are provided only for the purpose of illustrating the present disclosure, and thus the present disclosure is not limited thereto.

[0145] <Example>

[0146] Example 1

[0147] (1) Preparation of binder for anode

[0148] A monomer mixture comprising (a) 1,3-butadiene (40 parts by weight), (b1) α-methylstyrene (5 parts by weight), (c) acrylonitrile (25 parts by weight) and (d1) methacrylic acid (5 parts by weight); sodium lauryl sulfate (1.5 parts by weight) as an emulsifier; and potassium persulfate (0.5 parts by weight) as a polymerization initiator are added to water (150 parts by weight) as a solvent.

[0149] The mixture is heated to 60°C and subjected to polymerization reaction for 4 hours while maintaining 60°C, and then (d1) methacrylic acid (25 parts by weight) is further added, followed by polymerization reaction for about 5 hours, thereby obtaining an adhesive comprising a (co)polymer in the form of latex particles and water.

[0150] The total solid content of the obtained adhesive of Example 1 was 30%, and the average particle diameter of the latex particles measured using a particle size analyzer (NICOMP AW380, manufactured by PSS Corporation) was 167 nm.

[0151] (2) Preparation of anode mixture

[0152] Artificial graphite (85.38 parts by weight) and silicon dioxide (11 parts by weight) as anode active materials, carbon black (1 part by weight) and single-walled carbon nanotubes (0.02 parts by weight) as conductive materials, the binder (1.6 parts by weight) of Example 1 above, and carboxymethyl cellulose (1 part by weight) as a thickener were used and mixed in water as a dispersion medium while stirring for 1 hour. In this case, the slurry phase was adjusted so that the total solid content was 45% by weight, thereby obtaining the anode mixture of Example 1.

[0153] (3) Preparation of anode

[0154] A copper foil with a thickness of 10 μm was prepared and used as the anode current collector. The anode mixture of Example 1 was coated with 7.0 mg / cm2 of the anode current collector on each side using a comma coater. 2 The anode current collector was coated with a loading of 1000 μm on both sides of the anode current collector, dried with hot air in an oven at 80° C. for 10 minutes, and rolled to a total thickness of 93 μm. Thus, the anode of Example 1 was obtained.

[0155] (4) Preparation of secondary batteries

[0156] Lithium metal was used as the counter electrode. Specifically, a separator was inserted between the anode of Example 1 and the lithium metal, and the two were assembled. Then, an electrolyte was injected according to a method known in the art to complete a lithium ion half-cell.

[0157] As the electrolyte, LiPF 6 It was dissolved in a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) (weight ratio of EC:PC:DEC = 3:2:5) to a concentration of 1 M, and 2 parts by weight of vinylene carbonate (VC) was further added.

[0158] Example 2

[0159] A binder for an anode, an anode mixture, an anode, and a secondary battery of Example 2 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0160] Specifically, in Example 2, 1,3-butadiene (53 parts by weight), (b2) styrene (5 parts by weight), (c) acrylonitrile (19 parts by weight), and (d1) methacrylic acid (24 parts by weight in total, 5 parts by weight at the beginning / 19 parts by weight later) were used.

[0161] Example 3

[0162] A binder for an anode, an anode mixture, an anode, and a secondary battery of Example 3 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0163] Specifically, in Example 3, (a) 1,3-butadiene (55 parts by weight), (b1) α-methylstyrene (5 parts by weight), (c) acrylonitrile (20 parts by weight), (d2) acrylic acid (5 parts by weight at first) and (d1) methacrylic acid (17 parts by weight later) were used.

[0164] Example 4

[0165] A binder for an anode, an anode mixture, an anode, and a secondary battery of Example 4 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0166] Specifically, in Example 4, (a) 1,3-butadiene (48 parts by weight), (b2) styrene (2 parts by weight), (c) acrylonitrile (25 parts by weight), and (d1) methacrylic acid (25 parts by weight in total, 10 parts by weight at the beginning / 15 parts by weight later) were used.

[0167] Example 5

[0168] A binder for an anode, an anode mixture, an anode, and a secondary battery of Example 5 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0169] Specifically, in Example 5, (a) 1,3-butadiene (40 parts by weight), (b2) styrene (20 parts by weight), (c) acrylonitrile (15 parts by weight), and (d1) methacrylic acid (25 parts by weight in total, 5 parts by weight at the beginning / 20 parts by weight later) were used.

[0170] Comparative Example 1

[0171] A binder for an anode, an anode mixture, an anode, and a secondary battery of Comparative Example 1 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0172] Specifically, in Comparative Example 1, (a) 1,3-butadiene (50 parts by weight), (c1) acrylonitrile (25 parts by weight), and (d1) methacrylic acid (25 parts by weight) were used.

[0173] Comparative Example 2

[0174] A binder for an anode, an anode mixture, an anode, and a secondary battery of Comparative Example 2 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0175] Specifically, in Comparative Example 2, (a) 1,3-butadiene (45 parts by weight), (b2) styrene (25 parts by weight), (c1) acrylonitrile (25 parts by weight), and (d1) methacrylic acid (5 parts by weight) were used.

[0176] Comparative Example 3

[0177] A binder for an anode, an anode mixture, an anode, and a secondary battery of Comparative Example 3 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0178] Specifically, in Comparative Example 3, (a) 1,3-butadiene (40 parts by weight), (b2) styrene (58 parts by weight), and (d2) acrylic acid (2 parts by weight) were used.

[0179] Comparative Example 4

[0180] A binder for an anode, an anode mixture, an anode, and a secondary battery of Comparative Example 4 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0181] Specifically, in Comparative Example 4, (a) 1,3-butadiene (40 parts by weight), (c) acrylonitrile (30 parts by weight), and (d1) methacrylic acid (30 parts by weight) were used.

[0182] Comparative Example 5

[0183] A binder for an anode, an anode mixture, an anode, and a secondary battery of Comparative Example 5 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0184] Specifically, in Comparative Example 5, (a) 1,3-butadiene (40 parts by weight), (b2) styrene (30 parts by weight), and (d1) methacrylic acid (30 parts by weight) were used.

[0185] Comparative Example 6

[0186] A binder for an anode, an anode mixture, an anode, and a secondary battery of Comparative Example 6 were prepared in the same manner as in Example 1 except that the composition of the monomer mixture was changed.

[0187] Specifically, in Comparative Example 6, (a) 1,3-butadiene (45 parts by weight), (b2) styrene (40 parts by weight), (c) acrylonitrile (5 parts by weight), and (d1) methacrylic acid (5 parts by weight) were used.

[0188] The compositions of each of the binders for anodes of Examples 1 to 5 and Comparative Examples 1 to 6 are summarized in Table 1 below.

[0189] In the following Table 1, the first monomer represents (a) 1,3-butadiene, the second monomer represents (b1) α-methylstyrene or (b2) styrene, the third monomer represents (c) acrylonitrile, and the fourth monomer represents (d1) methacrylic acid or (d2) acrylic acid, respectively.

[0190] In addition, the content of the monomer is the content (wt%) based on the total weight (100 wt%) of the monomer.

[0191] [Table 1]

[0192]

[0193] Experimental Example 1: Evaluation of Binder for Anode

[0194] Each of the binders for anodes of Examples 1 to 5 and Comparative Examples 1 to 6 described above was evaluated under the following conditions and is summarized in Table 2 below.

[0195] Viscoelastic loss factor (tanδ) and storage modulus: After each binder for anode was molded into a film-like specimen, the viscoelastic behavior was measured using a dynamic mechanical analyzer (TA Instrument).

[0196] Specifically, the binder for the anode was dried to form a film with a thickness of 2 mm or less, and then the film was punched out into a rectangle of 18 mm (length)×6 mm (width) to prepare a sample.

[0197] In other words, the binder for anode was put into a Teflon mold, dried at room temperature for 24 hours, and then dried again with hot air at 80°C for 24 hours to prepare a film with a thickness of 2 mm or less. Thereafter, a sample was prepared by punching into a rectangle of the above size.

[0198] The specimen was placed in a dynamic mechanical analyzer (manufactured by TA Instrument) and the temperature was increased at a frequency of 1 Hz and 5°C / min in a film stretching mode to measure the viscoelastic behavior with respect to dynamic deformation at a shear strain with a strain amplitude of 0.1% at each measuring temperature (-60°C to 100°C).

[0199] During the measurement, the temperature (peak) at which the maximum value of the viscoelastic loss factor (tan δ) was reached was confirmed and recorded as tan δ (Tp) in Table 2 below, and the storage modulus at 100° C. was measured and shown in Table 2 below.

[0200] Furthermore, the storage modulus value at 100°C is divided by the storage modulus value at the glass transition temperature (Tp) to obtain the ratio of the storage modulus of the (co)polymer measured at 100°C to the storage modulus at the glass transition temperature (ie, Tp).

[0201] For reference, the dynamic mechanical analyzer can be used to confirm the behavior of the glass transition temperature, which is difficult to confirm in DSC due to the properties of the sample. From the results, it can be found that the higher the tanδ peak, the higher the Tg, the harder and the higher the strength; the lower the tanδ peak, the lower the Tg, the softer.

[0202] Average particle size of latex particles: After each binder for anode was diluted at room temperature so that the measured intensity value was about 300 (KHz), the average particle diameter was measured using a particle size analyzer (NICOMP AW380, manufactured by PSS) according to a dynamic light scattering method.

[0203] Specifically, distilled water was added to the binder for anode to dilute it, and then put into a particle size analyzer (NICOMP AW380, manufactured by PSS Corporation) to record the average particle size measured after 5 minutes.

[0204] Here, the average particle size refers to the arithmetic average particle size in a particle size distribution measured by a dynamic light scattering method, and the arithmetic average particle size corresponds to the average particle size of a scattering intensity distribution.

[0205] [Table 2]

[0206]

[0207] Referring to Table 2, it can be seen that compared with Comparative Examples 1 to 6, Examples 1 to 5 are superior in storage modulus.

[0208] Specifically, for Comparative Examples 1 to 6, it can be confirmed that any one of the first to fourth monomers is not used, or the amounts of the first to fourth monomers do not satisfy the limited range of the implementation scheme, so the storage modulus measured at 100° C. is low, less than 100 MPa, and the viscoelastic properties are also poor.

[0209] In addition, for Comparative Examples 1 to 6, it was confirmed that the ratio of the storage modulus of each (co)polymer measured at 100°C to the storage modulus at the glass transition temperature was 0.1 or less (ie, 10% or less).

[0210] In contrast, for Examples 1 to 5, it can be confirmed that the storage modulus measured at 100° C. is 100 MPa or more and the maximum peak temperature (Tp) of the viscoelastic loss factor (tan δ) is 0° C. or less because the first to fourth monomers are contained and their amounts satisfy the defined ranges in the embodiment.

[0211] In addition, for Examples 1 to 5, it was confirmed that the ratio of the storage modulus of each (co)polymer measured at 100°C to the storage modulus at the glass transition temperature was 0.1 or more (ie, 10% or more).

[0212] Experimental Example 2: Evaluation of anode and secondary battery

[0213] For Examples 1 to 5 and Comparative Examples 1 to 6, the anodes and the lithium secondary batteries were evaluated under the following conditions, respectively, and the results are recorded in Table 3 below.

[0214] Capacity retention rate of secondary battery after 30 cycles: In a thermostatic chamber at 25°C, the process of charging and discharging each prepared coin-type lithium secondary battery at 0.1C in a voltage range of 0 to 1V and at 0.1C was repeated 30 times, and the capacity retention rate (capacity retention rate after 30 cycles) is summarized in Table 3 below.

[0215] Adhesion of anode: For each of the above-mentioned examples and comparative examples, the peel strength was measured 5 times or more, and the average value thereof is shown in the following Table 2. In this case, the peel strength was measured as the force (gf) required to remove the tape from the anode at a peeling angle of 180° after the anode was bonded to a tape having a width of 20 mm using a tensile tester (Stable Micro System, TA-XT).

[0216] [Table 3]

[0217] Adhesion force of anode (gf / cm) Capacity retention rate of secondary battery after 30 cycles (%) Example 1 25 96 Example 2 21 96 Example 3 18 95 Example 4 22 96 Example 5 19 94 Comparative Example 1 12 90 Comparative Example 2 13 88 Comparative Example 3 6 85 Comparative Example 4 5 86 Comparative Example 5 12 89 Comparative Example 6 23 84

[0218] According to these results, in the case of an embodiment of the present disclosure, it can be found that even when the temperature rises, the storage modulus does not decrease significantly, so the elasticity is sufficient to withstand the volume change of the anode active material, thereby providing optimal elasticity within the temperature range of actual use. In addition, in the case of the embodiment, it can be found that the processing performance is improved and the thickness expansion of the electrode can be suppressed, thereby ensuring the excellent life of the secondary battery.

[0219] In addition to the description of the implementation scheme, the content of each monomer and the content ratio of the monomers are controlled with reference to the above-mentioned Examples 1 to 5, thereby adjusting the elasticity of the binder used for the anode compared with Comparative Examples 1 to 6, and ultimately adjusting the life of the secondary battery to the desired range.

Claims

1. A binder for an anode of a secondary battery, comprising a copolymer having a storage modulus of 100 MPa or more measured at 100° C., in, Based on the total weight of repeating units, the copolymer comprises: a) 35 to 60 wt% of a first repeating unit derived from an aliphatic conjugated diene first monomer; b) 0.1 wt % to 25 wt % of a second repeating unit derived from an aromatic vinyl-based second monomer; c) 10 to 35 weight percent of a third repeating unit derived from a nitrile third monomer; and d) 15 to 35% by weight of a fourth repeating unit derived from an unsaturated carboxylic acid-based fourth monomer, Wherein, the glass transition temperature of the copolymer is -60°C to 0°C, The ratio of the storage modulus of the copolymer measured at 100° C. to the storage modulus at the glass transition temperature is 10% or more.

2. The binder for an anode of a secondary battery according to claim 1, in, The storage modulus is measured by applying a shear strain having a frequency of 1 Hz and a strain amplitude of 0.1% to a film having a thickness of 2 mm or less including the copolymer within a temperature range of -60°C to 100°C and increasing the temperature at a heating rate of 5°C / min.

3. The binder for an anode of a secondary battery according to claim 1, in, When the viscoelastic behavior of the film with respect to dynamic deformation is measured in a temperature range of -60°C to 100°C and at a heating rate of 5°C / min, and a shear strain with a frequency of 1 Hz and a strain amplitude of 0.1% is applied, the maximum peak temperature Tp of the viscoelastic loss factor tanδ of the adhesive for the anode of the secondary battery is below 0°C.

4. The binder for an anode of a secondary battery according to claim 1, in, The first monomer is selected from 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,2-dimethyl-1,3-butadiene, 1,4-dimethyl-1,3-butadiene, 1-ethyl-1,3-butadiene, 2-phenyl-1,3-butadiene, 1,3-pentadiene, 1,4-pentadiene, 3-methyl-1,3-pentadiene, 4 At least one of methyl-1,3-pentadiene, 2,4-dimethyl-1,3-pentadiene, 3-ethyl-1,3-pentadiene, 1,3-hexadiene, 1,4-hexadiene, 1,5-hexadiene, 2-methyl-1,5-hexadiene, 1,6-heptadiene, 6-methyl-1,5-heptadiene, 1,6-octadiene, 1,7-octadiene and 7-methyl-1,6-octadiene.

5. The binder for an anode of a secondary battery according to claim 1, in, The second monomer is at least one selected from styrene, α-methylstyrene, β-methylstyrene, p-tert-butylstyrene, chlorostyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene and divinylbenzene.

6. The binder for an anode of a secondary battery according to claim 1, in, The third monomer is at least one selected from acrylonitrile, methacrylonitrile and allyl cyanide.

7. The binder for an anode of a secondary battery according to claim 1, in, The fourth monomer is at least one selected from acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, tetrahydrophthalic acid, crotonic acid, isocrotonic acid and nadic acid.

8. The binder for an anode of a secondary battery according to claim 1, in, The copolymer is a latex particle having an average particle size of 50 nm to 500 nm.

9. The binder for an anode of a secondary battery according to claim 1, Further comprising an aqueous solvent.

10. The binder for an anode of a secondary battery according to claim 9, in, The aqueous solvent may be included in an amount of 50 parts by weight to 1,000 parts by weight based on 100 parts by weight of the copolymer.

11. A method for preparing a binder for an anode of a secondary battery according to claim 1, comprising the following steps: The copolymer is prepared by emulsion polymerizing a monomer mixture in the presence of an emulsifier and a polymerization initiator, wherein the step of preparing the copolymer by emulsion polymerizing a monomer mixture in the presence of an emulsifier and a polymerization initiator is performed by multi-stage polymerization, Wherein, based on the total weight of the monomer mixture, the monomer mixture contains: a) 35 wt % to 55 wt % of an aliphatic conjugated diene first monomer; b) 0.1 wt % to 20 wt % of an aromatic vinyl second monomer; c) 15 wt % to 35 wt % of a nitrile third monomer; and d) 15 wt % to 35 wt % of an unsaturated carboxylic acid fourth monomer.

12. The method for preparing a binder for an anode of a secondary battery according to claim 11, in, The step of preparing the copolymer by emulsion polymerizing a monomer mixture in the presence of an emulsifier and a polymerization initiator comprises the following steps: In the presence of an emulsifier and a polymerization initiator, all of a) aliphatic conjugated diene first monomer, all of b) aromatic vinyl second monomer, all of c) nitrile third monomer and part of d) unsaturated carboxylic acid fourth monomer are first emulsion polymerized; and After the first emulsion polymerization, the remaining d) unsaturated carboxylic acid fourth monomer is added, and then the second emulsion polymerization is carried out.

13. The method for preparing a binder for an anode of a secondary battery according to claim 12, in, The part of d) the unsaturated carboxylic acid fourth monomer in the first emulsion polymerization and the remaining d) the unsaturated carboxylic acid fourth monomer in the second emulsion polymerization satisfy a weight ratio of 1:0.1 to 1:

10. 14 . An anode mixture for a secondary battery, comprising the binder for an anode of a secondary battery according to claim 1 and an anode active material.

15. The anode mixture for a secondary battery according to claim 14, in, The anode includes at least one anode active material selected from the group consisting of a carbonaceous material and a silicon compound.

16. An anode of a secondary battery, comprising: An anode mixture layer comprising the anode mixture of claim 14; and an anode current collector.

17. A secondary battery comprising the anode according to claim 16.

Citation Information

Patent Citations

  • Polyimide precursor solution, polyimide precursor, polyimide resin, mixture slurry, electrode, mixture slurry production method, and electrode formation method

    CN103429640A

  • Binder for secondary battery and electrode mixture for secondary battery

    JP6269890B1

  • Binder for Secondary Battery Providing Excellent Adhesion Strength and Cycle Property

    KR1020120014634A

  • KR20200045869A